2003
DOI: 10.1007/s00299-003-0646-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of an inducible reporter gene system for the analysis of auxin distribution in the moss Physcomitrella patens

Abstract: The plant hormone auxin plays a major role in a variety of growth and developmental responses, even in the more ancient plants-for example, cell differentiation in mosses. Nevertheless, almost nothing is known about the distribution of auxin during moss development. To address this question, we characterised auxin distribution in the moss Physcomitrella patens using auxin-inducible reporter gene systems. Stable transgenic Physcomitrella plants were produced expressing the beta-glucuronidase (GUS) gene driven b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 29 publications
4
72
0
Order By: Relevance
“…In situ immunolocalization experiments showed that actively proliferating apices of the filaments did have higher concentrations of IAA. Similar results have been obtained in filaments of the bryophyte Physcomitrella patens, where the expression of GH3::GUS and DR5::GUS transgenes indicates higher concentrations of auxin in the young, actively growing cells of the protonemal filaments (Bierfreund et al, 2003), similarly located at the apices (Cove et al, 2006). Therefore, a possible scenario in agreement with the data from the ablation experiment is that, in an intact filament, there is an IAA gradient that reaches its maximum at both extremities of the filament, where E cells are located.…”
Section: Role Of Auxin In E Siliculosus Developmentsupporting
confidence: 71%
“…In situ immunolocalization experiments showed that actively proliferating apices of the filaments did have higher concentrations of IAA. Similar results have been obtained in filaments of the bryophyte Physcomitrella patens, where the expression of GH3::GUS and DR5::GUS transgenes indicates higher concentrations of auxin in the young, actively growing cells of the protonemal filaments (Bierfreund et al, 2003), similarly located at the apices (Cove et al, 2006). Therefore, a possible scenario in agreement with the data from the ablation experiment is that, in an intact filament, there is an IAA gradient that reaches its maximum at both extremities of the filament, where E cells are located.…”
Section: Role Of Auxin In E Siliculosus Developmentsupporting
confidence: 71%
“…In order to discriminate between these alternatives, we compared the responses of GmGH3pro:GUS and PpSHI2pro:PpSHI2-GUS lines to exogenous auxin. As previously reported (Bierfreund et al, 2003;Fujita et al, 2008), the GmGH3 promoter was induced by auxin treatment in a concentrationdependent manner, which resulted in an almost uniform staining of the entire gametophore, suggesting that all cell types can respond to auxin (Decker et al, 2006) (Fig. 2).…”
Section: Ppshi1/2 Expression Coincides With Sites Of Auxin Responsementioning
confidence: 51%
“…The PpSHI1/2 expression pattern in the adult gametophore, with maxima in rhizoids and axillary hairs, is almost identical to that of a GmGH3pro:GUS reporter [Gm, Glycine max (soybean)] used to detect sites of auxin response (Bierfreund et al, 2003;Fujita et al, 2008). If not coincidental, this correlation could indicate that the PpSHI genes are induced by auxin, or that their expression is a prerequisite for the generation of auxin peaks or auxin responsiveness.…”
Section: Ppshi1/2 Expression Coincides With Sites Of Auxin Responsementioning
confidence: 85%
“…A tetracyclinerepressible gene-expression system has been reported in P. patens (Zeidler et al, 1996), but it requires continuous growth on tetracycline, which is detrimental to the moss (Laloue M., personal communication). Abscissic acid or auxin-induced gene expression have also been shown using, respectively, the wheat Em gene promoter (Knight et al, 1995) or the soybean GH3 gene promoter (Bierfreund et al, 2003). However, the use of phyto-hormone-regulated gene expression may interfere with the plant physiology and remain unfit for a general versatile conditional gene-expression system in plants.…”
Section: Introductionmentioning
confidence: 99%